PENGARUH SUBSTITUSI TEPUNG BERAS MERAH TERHADAP KUALITAS KUE SUS - YANTI, RAHMI; Ruaida, Ruaida; Faridah, Anni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2014)
The use of red rice flour in food processing is an attempt to diversify the food, one of them is in the processing of eclairs . One of the hallmarksof red rice flour that contains aleuroneproducing anthocyanin containing nutrients and fiber that are important for the body. So with the use of red rice flour in eclairs processed to improve the quality of the eclairs. This study aimed to analyze the effect of different composition of red rice flour as much as 0%, 15%, 30%, and 45% of the quality of the volume, shape, color, texture, aroma, flavor and hedonic eclairs. Test and hedonic quality levels at better quality volume is at 15% substitution. Level of test quality and the color, aroma, and taste better at 45% substitution and hedonic test the quality of the color, aroma, and taste better at 15% substitution. Test quality levels better texture at 15% substitution and hedonic test better texture at 30% substitution. Keywords : Red Rice Flour, Quality Sus, substitution, Organoleptikc